Traceability in food supply chains: Review and SME focused analysis - Curto, João Paulo (2022)
Traceability can be a tool for safety and quality assurance for food perishables as well as for process optimization and economic gain. However, it is often considered mere bureaucracy and an economic burden. Such is prevalent in small and medium-sized enterprises. As they constitute most of food sector, the adoption of traceability systems is quite slow and mostly to satisfy legal requirements. To determine the main advantages and disadvantages of traceability models, implementation and technologies, a literature review and Small and Medium Enterprises (SME) focused analysis was performed in the part I of this study. In Part II, a low cost open-source traceability focused on food safety and quality is developed. It is based on HACCP flowcharts to define gateways for quality evaluation and encompasses external verification and product history maintenance. Economic gains, more quality and safety, better efficiency and a more direct contact with consumers are some of the main advantages. High implementation costs, poorly defined benefits, lack of compatibility, consumer focused perspective and exposure of sensitive information are some of the main issues. This study serves to expose these issues and suggest solutions, aiming to encourage the adoption of traceability systems, with last-end benefits to producers, retailers, and consumers.